Mengurai Permasalahan Pengembangan Koperasi Syariah di Lombok - Kharisma Rindang Sejati (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2021)
Sharia cooperative has become an alternative to restoring the economic conditions in Lombok, particularly for providing the capital to the small entrepreneurs. The massive development of the Sharia economic sector has led NTB provincial government to intensify the development of sharia economic system through sharia cooperatives. Despite the massive support from the local government, Sharia Cooperative still has several problems, both internally and externally. This article aims to identify the dominant factors that obstruct the development of Sharia cooperative in Lombok, by using the Analytic Network Process (ANP) method approach. The results shows that the main problem is the unqualified human resources as indicated by the level of suitability or agreement between the respondents based on the Kendall coefficient, Kendall coefficient (W) on the priority aspects of the problem for respondents consisting of regulators, root and academics, relatively on high number , around W = 0.725. This data shows that the regulators, the practitioners, and the academics on the same position regarding the main problem that impede developing Islamic cooperatives in Lombok.